Standards and Waste: Valuing Food Waste in Consumer Markets - Nadine Arnold (Worldwide Waste, 2022)
Standards drive waste accumulation, which is particularly evident in the case of food. This article illuminates how food that is discarded due to failed standardized expectations is valued in consumer markets. Theoretically oriented by insights from the sociology of standards and valuation studies, it examines three Swiss organizational initiatives that successfully value food waste. Based on rich qualitative data, the article compares the three valuation processes and finds two central commonalities. On the one hand, the initiatives replace the valuation based on product standards with sensory experience. On the other, the initiatives employ additives that buttress the valuation process. These additives include additionally purchased food that enable the processing of the waste and various judgment devices that help consumers in judging the valued food waste. While improving our knowledge of how waste turns into food again, the article’s main contribution lies in bringing the nexus between standards and waste to our attention.